Influência da dieta sobre a alteração populacional de Moenkhausia dichroura, no reservatório de Manso, Estado de Mato Grosso, Brasil. - Silva, Marlene Rodrigues da (2008)
This study aims to analyze the diet and morphological aspects of Moenkhausia dichroura, relating these features with species? abrupt abundance in the Manso Reservoir, Mato Grosso State. The diet was compared spatially (Montante, Reservatório and Jusante) and temporally (Phase I = first year of damming and Phase II = fourth year of damming. Stomach contents of 392 fishes were analyzed and the diet was described through of the volumetric representation of the food category. In the upstream this species showed tendency to insectivory (V% = 51.46% of aquatic insects in the Phase I and V% = 29.95 of terrestrial insects in the Phase II), in the reservoir to zooplanktivory (V% = 77.11 and V% = 64.73 of microcrustaceans, in the Phases I and II, respectively) and in the downstream to herbivory (V% = 56.02 and V% = 62.84 of plants in the Phases I and II, respectively). Was verify significant spatial differences in the diet (H= 197.11, p < 0.05), through of the non-parametric Kruskal-Wallis test. Significant temporal differences was verify between diet of the individuals of Montante I and Montante II (p < 0.05) through of the a posteriori Tukey test. In relationship to the morphological aspects, this species show many gill rakers that are long and close together, evidencing filtering capacity. There was abrupt increase of M. dichroura abundance during of field study, mainly in fourth year of damming, inside the reservoir. This fact seems to be closely related with the high abundance and availability of zooplankton in the dammed environment and also with ability of the species to exploit this resource.